Analysis of Hadith on "Poverty" and Its Correlation with the Hadith of "Production" (Study of the Thought Ali Mustafa Yaqub) - Fatah, Hairil (Jurnal Hukum Ekonomi Syariah, 2024)
Ali Mustafa Yaqub said that the hadith "poverty almost gives rise to disbelief" is weak or wrong. However, there is a hadith of the Prophet Saw., which asks to be kept away from poverty. Because poverty causes impacts such as crime, violence, theft, or loss of (religious) belief. So, hadiths about poverty essentially have the message that being productive is mandatory, just as the Prophet Saw., recommended production in managing land. The aim of this research is to find out Ali Mustafa Yaqub’s thoughts about hadiths that talk about poverty and their correlation with production hadiths: farming. The method used is qualitative with the type of library research with primary and secondary sources from various literature. The results of the research show that Ali Mustafa Yaqub’s thoughts about the hadith "poverty almost makes disbelief" are weak or false, because it was narrated byÂ Yazid bin Aban al-Raqqasyi who was accused of lying. Also, the Prophet SAW., asked to be kept away from poverty, This means that poverty will have a negative social and religious impact, does not claim (demands) the possibility of impacting one’s faith. So that the hadith about poverty is understood not as a matter of whether it is true or not, but the meaning behind it is a recommendation to actively innovate, creativity, and productive in any way, including production, managing land. So that Muslims become an economically strong people, and are free from the shackles of poverty.